Interview with Ashley Mears, author of Pricing Beauty: The Making of a Fashion Model: “Things May Look Great and Glamorous on the Outside, but There is Much More Work behind This” (interviewed by Tamara Kusimova) - Mears, Ashley (Экономическая социология, 2017)
Ashley Mears is an associate professor in the Sociology Department and the Women’s, Gender & Sexuality Studies Program at Boston University. In her studies, Dr. Mears focuses on the nexus of culture and markets. In her teaching and research, she generally explores how people assign value to things and focuses on how gender, race, and class in equities inform the production and evolution of culture. Dr. Mears’ first book, Pricing Beauty: The Making of a Fashion Model (2011) was widely recognized not only in academic circles, but also with popular readers. The book is devoted to sociological inquiry into the fashion-model business. Modeling is a specific kind of market in which careers depend on judgments about individual appearance. Based on ethnographic work and interviews, the book uncovers how the modeling industry produces value from female bodies and beauty. The review of «Pricing Beauty» was published in the Journal of Economic Sociology in 2014 (15 (5): 113–122). Her current research is focused on how the VIP leisure and party scene operates as a global market. Based on ethnographic observations and a series of interviews, Dr. Mears examines how elites use different repertoires of symbols, values, and practices to signal status among each other. In the following interview, Dr. Mears speaks about current changes in the fashion industry, the new politics of diversity, and feminist research practices and methodology. She also reveals details from her upcoming new book. Dr. Mears was interviewed by Tamara Kusimova, a research assistant and a sociology master’s student at the Laboratory for Studies in Economic Sociology in Higher School of Economics, Moscow.